فتوى الجمعة تأليف إدريس بن مولاي المهدى بن مولاي إبراهيم "ت. حوالي 1354 هـ." - مولاى إبراهيم، إدريس بن مولاى المهدى، ت. 1354 هـ.; بونعامة، منى (مركز جمعة الماجد للثقافة والتراث - قسم الدراسات والنشر والشؤون الخارجية, 2017)
Our work is part of the efforts to contribute to bridging some of the existing gaps in the scarcity of Mauritania’s historical resources on the country’s past through the study and editing one of the important fatwas that stores aspects of the silent history of the country. Which is entitled : “The invalidation of Friday prayers in the village of Walata and other villages of Saybah ” by the author Sharif Idris bin Moulay Mahdi bin Moulay Ibrahim died around (1354 AH) Which chronicles an era of intellectual conflict in the Houdh region in the far east of Mauritania. This Fatwah was elected for several considerations, the most important of which are: - The fact that the fatwa dates back to a historical stage that was steeped in events and political and intellectual conflicts and logical controversies that have weighed 011 the lives of the population, and the Bedouin desert jurisprudence (Fiqh of the Badia) and its abundance were fed with many jurisprudential dilemmas and intellectual narratives between the jurisprudents and philosophers, who were divided in ways that, at the time, were very damaging to the root of the intellectual conflict rooted in the region. - To focus on the country’s elite scholars, especially those whose biographies have not been entered in books of biography and they have not received the attention of scholars.
Keywords: أصول الفقه الإسلامى -- صلاة الجمعة -- فقه النوازل -- الفتوى الإسلامية -- موريتانيا